Assessment of post-harvest fish losses among small-scale fishermen in Ondo State, Nigeria - Bukola, Adelaja Olusumbo Adeolu (2018)
Post-harvest losses need to be addressed in order to ensure balance of food demand and supply. Small-scale fisheries has been identified as one of the sectors with high postharvest losses among food production sub-sectors. In Nigeria, small-scale fisheries subsector has been neglected despite its significant contribution to local fish production. Hence, this study aims to estimate the magnitude of post-harvest losses, their handling practices, possession of storage facilities and analyse the factors that influence postharvest fish losses among small-scale fishermen in Nigeria particularly in Ondo State. A survey was conducted on 400 small-scale fishermen from 20 fishermen communities along the coastal area of Ondo State. The data were analysed using descriptive statistics like frequency, percentage and standard deviation; fish loss model for three dominant marine fish species {croaker (Pseudotolithus spp.), catfish (Arius spp.) and shrimp (Nematopalaemon spp.)}; and multiple regression model. The findings show that smallscale fishermen lack access to ice, suitable covering materials and storage facilities in the process of transporting fish from the fishing ground to the landing site. The fishermen incur average post-harvest fish losses of 8.15 percent for croaker, 7.76 percent for catfish and 7.57 percent for shrimp. Regression model indicates that variables such as age, educational level, fishing experience, credit facilities, fish training, duration of fishing cycle, storage facilities and transportation facilities are statistically significant in determining post-harvest fish losses in the study area. Consequently, the government should provide suitable infrastructural facilities such as ice blocks, covering materials and storage facilities to small-scale fisheries to reduce post-harvest losses. The government should formulate suitable policies to develop the small-scale fisheries sub-sector, and fishermen should be trained on the appropriate post-harvest handling techniques to enhance the livelihood of small-scale fishermen.